Association of interleukin-6 gene polymorphism (rs1800796) with severity and functional status of osteoarthritis in elderly individuals. Issue 2 (October 2015) - Fernandes, Marcos T.P.; Fernandes, Karen B.P.; Marquez, Audrey S.; Cólus, Ilce M.S.; Souza, Marilesia F.; Santos, João Paulo M.; Poli-Frederico, Regina C.
Highlights Individuals carrying the C allele of IL6 gene have lower susceptibility to osteoarthritis. The C allele of IL6 gene was associated with minor radiological impairment in hip and knee osteoarthritis. Patients with osteoarthritis with C allele of IL6 gene have better functional status according to WOMAC questionnaire. Individuals harboring GC or CC genotypes of IL6 gene have a reduction in IL-6 serum levels.